Analysis of the Effects of Interactive Multimedia, Student Perception, and Class Participation on the Improvement of Learning Outcomes in Online Learning - Labusab Labusab (Journal of Electrical Engineering and Informatics, 2026)
This study aims to analyze the effects of interactive multimedia, student perception, and class participation on the improvement of learning outcomes in online higher education. The focus is on students at Universitas Negeri Makassar, examining how these three factors collectively and individually influence academic achievement in a fully online learning environment. A quantitative approach was employed using a survey method. The population consisted of active undergraduate students enrolled in online courses, with 150 respondents selected through purposive sampling. Data were collected via validated questionnaires measuring the frequency and quality of multimedia use, students’ perceptions of online learning, class participation, and academic achievement. Descriptive statistics summarized the data, while multiple regression analysis was used to test the significance and magnitude of the relationships among variables. The findings indicate that interactive multimedia (β = 0.35, p < .001), student perception (β = 0.28, p < .001), and class participation (β = 0.30, p < .001) each positively and significantly affect learning outcomes. Collectively, these variables explain 63% of the variance in academic achievement, demonstrating that all three factors are critical in enhancing students’ performance in online courses. This study provides empirical evidence on the combined effect of multimedia interactivity, student perception, and participation in improving learning outcomes in online higher education. It contributes to understanding how integrated instructional strategies can optimize digital learning, offering practical guidance for educators in Indonesian universities and similar contexts worldwide.